UTILIZATION OF THE INTERNET OF THINGS IN CREATING SMART LIBRARIES AND INCREASING STUDENTS' INTEREST IN READING - Herni Ramayanti; Yetnimar; Peni Astuti; Septian Simatupang; Aloysius Eka Wenats (JURNAL ILMIAH EDUNOMIKA, 2025)
Abstract This study is a qualitative study with a descriptive approach, namely approaching the description of the main parts used in this article. In this case, the main parts in question are the Internet of Things and Smart Library. The data used in this article is secondary data that researchers obtain from sources indirectly obtained or it can be said that researchers obtain from credible quotations such as Books, Journals, and Websites. After the data is collected, the existing data is reduced, selected, and conclusions are drawn. The result in this article show that Internet of Things in creating a smart library that has four concepts and has been proposed by researchers above can be achieved easily. With a good Internet of Things, the internet network will be stronger and wider. The references owned are also increasing and in accordance with the needs and desires of students. This can make students happy and increase their interest in reading. Keywords: Internet of Things, Smart Library, Students